The Influence of Motivation, Incentives, and Work Discipline on Employee Performance in the Finance Department of Bandung Adventist Hospital - Filippus Cahyo Setyawan; Freddy Johanis Rumambi; Sri Sundari; Marisi Pakpahan; Bambang Rismadi (Digital Innovation : International Journal of Management, 2025)
This study aims to analyze the influence of motivation, incentives, and work discipline on employee performance in the Finance Department of Bandung Adventist Hospital. The method used is multiple linear regression analysis to determine the relationship between independent variables (motivation, incentives, and work discipline) and the dependent variable (employee performance). The analysis results indicate that motivation has a significant and positive effect on employee performance, with a regression coefficient of 0.326 and a significance level of 0.009, supporting the hypothesis that motivation plays an important role in enhancing employee productivity and commitment. Conversely, the incentive and work discipline variables show a negative and non-significant effect on performance, with coefficients of -0.162 and -0.208, respectively. This suggests that the current incentive and work discipline practices are not fully effective or do not meet employee expectations. Simultaneously, the three independent variables have a significant effect on employee performance, with the F-test showing a significance level of 0.009. This study recommends that management prioritize motivation improvement through training programs, rewards, and the development of a supportive work environment. Additionally, it is essential to evaluate the incentive system and adopt a more flexible disciplinary approach to align with employee needs and expectations.